Matematika/Evoliutė ir evolventė: Skirtumas tarp puslapio versijų

:<math>=2\cdot \frac{3(1+y'^2)^2 y' y''^2-(1+y'^2)^3 y'''}{y''^3}=2\cdot (1+y'^2)^2 \cdot \frac{3 y' y''^2-(1+y'^2) y'''}{y''^3}=</math>
:<math>=2\cdot (1+y'^2)^2 \cdot \frac{3 y' y''^2 - y''' - y'^2 y'''}{y''^3}.</math>
:Dalindami abi lygybės dalis iš :<math>2R=\frac{2(1+y'^2)^{3\over 2}}{y''},</math> gausime:
:<math>\frac{dR}{dx}= (1+y'^2)^{1\over 2} \frac{3 y' y''^2 - y''' - y'^2 y'''}{y''^2}.</math>
:Pakėlę kvadratu, gausime:
5 067

pakeitimai